Analisis Efektivitas Dan Efisiensi Anggaran Belanja Langsung Perwakilan Badan Kependudukan Dan Keluarga Berencana Nasional Provinsi Jawa Barat Tahun Anggaran 2016-2020 - Nadia Resti Oktaviani; Vina Citra Mulyandani (Indonesian Accounting Literacy Journal, 2022)
In the Representatives of BKKBN of West Java Province as one of the government's institutions that uses funds from the public sector in carrying out its programs and hopes that all activities are following the criteria for efficiency in the use of resources and effective in achieving the goals/targets that had been established. The purpose of this study discusses the level of effectiveness and efficiency of Direct expenditure budget in the Representatives of BKKBN of West Java Province. The method used is quantitative descriptive, namely by analyzing data targets, budget realization and direct expenditure budget realization for 2016-2020. The criteria of effectiveness and efficiency in Direct expenditure budget of the Representatives of BKKBN of West Java Province is varied, the average level of effectiveness is 83.58%, which shows the criteria obtained are quite effective and the average level of efficiency is 77.28%, which shows the criteria obtained are efficient.